Diabetic ketoacidosis in a pediatric intensive care unit - Clarice L.S. Lopes; Paula Pitta Pinheiro; Luzia S. Barberena; Guilherme U. Eckert (Elsevier, 2017)
Objective: To describe the characteristics of children aged 0-14 years diagnosed with diabetic ketoacidosis and compare the following outcomes between children with prior diagnosis of type 1 diabetes mellitus and children without prior diagnosis of type 1 diabetes mellitus length of hospital stay, severity on admission, insulin dosage, time of continuous insulin use, volume of fluids infused during treatment, and complications. Methods: A retrospective descriptive study with review of medical records of patients admitted to the pediatric intensive care unit of a referral hospital from June 2013 to July 2015. The following data regarding 52 admissions were analyzed: age, sex, weight, body surface area, signs, symptoms and severity on admission, blood gas, blood glucose, glycated hemoglobin, serum osmolarity, and index of mortality. The insulin dosage, time of continuous insulin use, volume administered in the expansion phase and in the first 24 h, length of stay, and complications such as electrolyte disturbances, hypoglycemia, cerebral edema, and death were compared between the two groups. Results: Patients without a previous diagnosis of DM1 were younger at admission, with mean age of 8.4 years (p < 0.01), reported more nausea or vomiting, polydipsia and polyuria, and showed more weight loss (p < 0.01). This study also observed a higher prevalence of hypokalemia (p < 0.01) and longer hospital stay in this group. Conclusions: No differences in severity between groups were observed. The study showed that children without prior diagnosis of type 1 diabetes mellitus were younger at admission, had more hypokalemia during the course of treatment, and had greater length of hospital stay. Resumo: Objetivo: Descrever as características de pacientes de zero a 14 anos admitidos com diagnóstico de Cetoacidose Diabética e comparar desfechos entre os pacientes com diabete melito tipo 1 prévio e aqueles sem diabete melito tipo 1 prévio: tempo de internação, gravidade na admissão, dose de insulina utilizada, tempo de insulinização contínua, volume de líquido infundido durante o tratamento e complicações. Métodos: Estudo descritivo retrospectivo com revisão de prontuários de pacientes internados na UTI pediátrica de um hospital de referência no período de junho de 2013 a julho de 2015. Analisamos os seguintes dados referentes a 52 internações: idade, sexo, peso, superfície corporal, sinais, sintomas, gravidade na admissão, gasometrias, glicemia, hemoglobina glicada, osmolaridade sérica e índice de mortalidade. As crianças com diabete já diagnosticado foram comparadas com aquelas sem diagnóstico prévio quanto à dose de insulina, tempo de insulinização continua, volume infundido na fase de expansão e nas primeiras 24 horas, tempo de internação e complicações como distúrbios hidroeletrolíticos, hipoglicemia, edema cerebral e morte. Resultados: Os pacientes sem diagnóstico prévio de DM I eram mais jovens no momento da admissão, com média de idade de 8,4 anos (p < 0,01). Relataram mais sintomas como vômitos, polidipsia e poliúria e apresentaram mais perda de peso (p < 0,01). Observamos maior prevalência de hipocalemia (p < 0,01) e maior tempo de internação no grupo acima citado. Conclusões: Não observamos diferenças quanto a gravidade entre os grupos. Pacientes diabéticos prévios eram mais jovens na admissão, apresentaram mais hipocalemia durante o tratamento e permaneceram mais tempo internados. Keywords: Diabetic ketoacidosis, Children, Cerebral edema, Mortality, Diabetes mellitus, Palavras-chave: Cetoacidose diabética, Crianças, Edema cerebral, Mortalidade, Diabetes mellitus